2016
DOI: 10.18180/tecciencia.2017.22.3
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Analysis of a Coanda-Effect Ejector Using CFD

Abstract: This work presents the optimization of a Coandă-effect air ejector used widely in industry through computational fluid dynamics. This optimization was developed in ANSYS FLUENT® software V16.2. Two 3D models of the commercial ejector (ZH30-X185 by SMC®) were carried out for the simulation procedure, varying the size of the separation of 0.3 and 0.8 mm in the walls of the nozzle, which communicates the high-pressure region and the mixture zone. In the experiment designed, the feed pressure applied to the ejecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Figure 12 shows that the entrainment ratio gradually decreases as the primary pressure increases from 0.3 MPa to 0.7 MPa. When the mainstream pressure is fixed, the entrainment ratio decreases continuously as the nozzle clearance increases from 0.1 mm to 0.5 mm; a similar trend was obtained elsewhere [30]. It also can be seen that when the primary pressure is 0.3 MPa, the entrainment ratio increases by 42.3% as the nozzle clearance increases from 0.1 mm to 0.15 mm, and the entrainment ratio rises by 85.9% when the nozzle clearance increases from 0.1 mm to 0.5 mm.…”
Section: Influence Of Mixing Chambersupporting
confidence: 83%
See 1 more Smart Citation
“…Figure 12 shows that the entrainment ratio gradually decreases as the primary pressure increases from 0.3 MPa to 0.7 MPa. When the mainstream pressure is fixed, the entrainment ratio decreases continuously as the nozzle clearance increases from 0.1 mm to 0.5 mm; a similar trend was obtained elsewhere [30]. It also can be seen that when the primary pressure is 0.3 MPa, the entrainment ratio increases by 42.3% as the nozzle clearance increases from 0.1 mm to 0.15 mm, and the entrainment ratio rises by 85.9% when the nozzle clearance increases from 0.1 mm to 0.5 mm.…”
Section: Influence Of Mixing Chambersupporting
confidence: 83%
“…Alexandru et al developed a semiempirical formula for two-dimensional Coanda flow while the curvature of the tangential momentum equation was neglected [16]. Sierra del Rio et al designed a two-ejector model with varying nozzle clearance (0.3 mm and 0.8 mm) to investigate the effect of nozzle clearance on the flow velocity by means of CFD methods [30]; their results showed that the velocity increases with the increase of nozzle clearance. Similar trends were obtained by Lowry et al based on a new Coanda ejector [31].…”
Section: Introductionmentioning
confidence: 99%